Peak phosphorus – peak food? The need to close the phosphorus cycle. (1st June 2013) - Rhodes, Christopher
The peak in the world production of phosphorus has been predicted to occur in 2033, based on world reserves of rock phosphate (URR) reckoned at around 24, 000 million tonnes (Mt), with around 18, 000 Mt remaining. This figure was reckoned-up to 71, 000 Mt, by the USGS, in 2012, but a production maximum during the present century is still highly probable. There are complex issues over what the demand will be for phosphorus in the future, as measured against a rising population (from 7 billion to over 9 billion in 2050), and a greater per capita demand for fertiliser to grow more grain, in part to feed animals and meet a rising demand for meat by a human species that is not merely more populous but more affluent. As a counterweight to this, we may expect that greater efficiencies in the use of phosphorus – including recycling from farms and of human and animal waste – will reduce the per capita demand for phosphate rock. The unseen game changer is peak oil, since phosphate is mined and recovered using machinery powered by liquid fuels refined from crude oil. Hence, peak oil and peak phosphorus might appear as conjoined twins. There is no unequivocal case that we can afford to ignore the likelihood of a supply-demand gap for phosphorus occurring sometime this century, and it would be perilous to do so.